Relationship between Frequency of Urinary Catheter Care and Incidence of Urinary Tract Infection - Nurianto, Henes; Isro'in, Laily; Mas'udah, Anni Fithriyatul (Health Gate, 2024)
Urinary tract infection (UTI) is a frequent occurrence in hospitals and it was reported that 37% of inpatients at RSU Muhammadiyah Ponorogo were fitted with urinary catheters and 38% of them experienced UTI. Frequency of urinary catheter care could potentially affect the incidence of UTI. This study aims to determine the relationship between the frequency of urinary catheter care and the incidence of urinary tract infection (UTI) in the KH Ahmad Dahlan Room of RSU Muhammadiyah Ponorogo. This research method is quantitative with a correlational design using a Cross Sectional approach. The study population was all inpatients in the KH Ahmad Dahlan Room at RSU Muhammadiyah Ponorogo in September - October 2023 totaling 484 patients with an average of 242 people / month. The sampling technique used purposive sampling with the research sample being a portion of inpatients with catheters installed, totaling 30 respondents. Data collection using Check List. Data analysis techniques using Chi-Square. The results of this study showed that of the 30 respondents, most of the 28 respondents (93.33%) with the frequency of urinary catheter care were irregular (not every day) and most of the 29 respondents (96.67%) experienced the incidence of urinary tract infections (UTI). The results of the Chi-Square statistical test obtained a p-value obtained of 0.095> 0.05 so as not to reject H0 which means there is no significant relationship between the frequency of urinary catheter care and the incidence of urinary tract infection (UTI).